Parametric Optimization of Organic Rankine Cycle with R245fa/R601a as Working Fluid - 朱家玲 康振华 安青松 李太禄 (Transactions of Tianjin University, 2015)
In order to select the appropriate working fluids and optimize parameters for medium-temperature geothermally-powered organic Rankine cycle （ORC）, R245fa is mixed with R601 a at geothermal water temperature of 110℃. Based on thermodynamics, the characteristics of mixture and its influence on the performance of ORC under different evaporating temperatures and composition proportions are analyzed. Results show that the zeotropic mixture R245fa/R601a （0.4/0.6） has the highest performance. When the evaporating temperature reaches 67 ℃, the outlet temperature of geothermal water is 61℃, the net power output is the highest and the thermal efficiency is about 9%.